FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU IBU RUMAH TANGGA MELAKUKAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) - Alvita Brilliana R. Arafah; Hari Basuki Notobroto (Universitas Airlangga, 2017)
Breast cancer is cancer with the number of new cases and deaths highest in Indonesia. According to the Data Center and Information Ministry of a health Indonesia in the year 2013, the number of new cases of breast cancer of 819 and the number of deaths amounted to 217. In general, breast cancer known after stepping on an advanced stage. So the methods of early detection of breast cancer are focused on the detection of early stage tumors that are usually small with self-breast examination (SADARI). The purpose of this research is to predict the factors related to the behavior of self-breast examination (SADARI) the housewives aged 40–50 years. This research is an observational study with cross sectional approach. Sample research totaling 100 people housewife in Kelurahan Sidotopo Wetan Kenjeran Subdistrict Surabaya. The measurement was done by providing a questionnaire to obtain information about the research variables. Variable independent research is k nowledge, attitudes, information accessibility, support health providers and descent with breast cancer. The results of this research showed the variables that are associated with the SADARI behavior of the housewifes is attitude (p = 0.000), accessibility of information (p = 0.000), and health care providers support (p = 0.010). The majority of housewives in Kelurahan Sidotopo Wetan Kenjeran Sub-district Surabaya showed a good attitude and support toward SADARI. In the area surrounding the residence h ousewife get access information easily. There are no support for doing SADARI from health care providers.